Effect of AlF3 on the density and elastic properties of zinc tellurite glass systems - Abd. Aziz, Sidek; Shaharuddin, Rosmawati; Mohamed Kamari, Halimah; Matori, Khamirul Amin; Talib, Zainal Abidin (MDPI AG, 2012)
This paper presents the results of the physical and elastic properties of the ternary zinc oxyfluoro tellurite glass system. Systematic series of glasses (AlF3)x(ZnO)y(TeO2)z with x = 0–19, y = 0–20 and z = 80, 85, 90 mol% were synthesized by the conventional rapid melt quenching technique. The composition dependence of the physical, mainly density and molar volume, and elastic properties is discussed in term of the AlF3 modifiers addition that are expected to produce quite substantial changes in their physical properties. The absence of any crystalline peaks in the X-ray diffraction (XRD) patterns of the present glass samples indicates the amorphous nature. The addition of AlF3 lowered the values of the densities in ternary oxyfluorotellurite glass systems. The longitudinal and transverse ultrasonic waves propagated in each glass sample were measured using a MBS8020 ultrasonic data acquisition system. All the velocity data were taken at 5 MHz frequency and room temperature. The longitudinal modulus (L), shear modulus (G), Young’s modulus (E), bulk modulus (K) and Poisson’s ratio () are obtained from both velocities data and their respective density. Experimental data shows the density and elastic moduli of each AlF3-ZnO-TeO2 series are found strongly depend upon the glass composition. The addition of AlF3 modifiers into the zinc tellurite causes substantial changes in their density, molar volume as well as their elastic properties.